CRITICAL READING STRATEGIES TO FOSTER STUDENTS’ CRITICAL THINKING - MASLAKHATIN, MASLAKHATIN (Buana Pendidikan, 2016)
Students’ critical thinking skills need to be developed, in particular in higher education to efficiently meet the 21st century learning skills. This can be undertaken when learning how to read. In this instance, the students should employ their critical reading strategies. To foster the critical thinking skills, the students can use critical reading strategies. Argumentative text is chosen in this study since students in higher education should be able to write scientific paper such as thesis and journal article. This library study aims to describe how critical reading strategies enhance the students’ critical thinking. They include (1) Annotating, (2) previewing, (3) scanning and skimming, (4) fact vs. opinion, (5) drawing conclusion, (6) questioning, (7) summarizing, and (8) paraphrasing. The writers conclude that teaching critical reading strategies may be able to help the students to improve their critical reading, critical thinking, and higher order thinking skills (HOTS). Besides, by utilizing critical reading strategies, the students will be able to increase the deep understanding beyond the text.